1999
DOI: 10.1097/00005768-199909000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exercise training on physiological and performance changes with weight loss in men

Abstract: These data indicate that a weight-loss dietary regimen in conjunction with aerobic and resistance exercise prevents the normal decline in fat-free mass and muscular power and augments body composition, maximal strength, and maximum oxygen consumption compared with weight-loss induced by diet alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
130
2
10

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(154 citation statements)
references
References 26 publications
12
130
2
10
Order By: Relevance
“…It is indeed possible that our male obese subjects were more sedentary than their female counterparts, since baseline maximal oxygen consumption normalized to the fat-free mass was higher in the latter group with respect to the former (47.8 vs 41.8 ml/min/kg). The fat-free mass reductions reported here and in our previous study (Sartorio et al, 2004a) for male subjects (B3 kg) are very similar to the losses observed in obeseoverweight men following 12-16 weeks of diet (Kraemer et al, 1999;Cox et al, 2003) or diet plus aerobic exercise (Hagan et al, 1986). In obese children, fat-free mass reduction during a 3-week BWR program similar to that adopted here has been recognized as a major factor for later regain in body weight (Schwingshandl & Borkenstein, 1995).…”
Section: Discussionsupporting
confidence: 84%
“…It is indeed possible that our male obese subjects were more sedentary than their female counterparts, since baseline maximal oxygen consumption normalized to the fat-free mass was higher in the latter group with respect to the former (47.8 vs 41.8 ml/min/kg). The fat-free mass reductions reported here and in our previous study (Sartorio et al, 2004a) for male subjects (B3 kg) are very similar to the losses observed in obeseoverweight men following 12-16 weeks of diet (Kraemer et al, 1999;Cox et al, 2003) or diet plus aerobic exercise (Hagan et al, 1986). In obese children, fat-free mass reduction during a 3-week BWR program similar to that adopted here has been recognized as a major factor for later regain in body weight (Schwingshandl & Borkenstein, 1995).…”
Section: Discussionsupporting
confidence: 84%
“…In adults, weight training has been shown to be superior to aerobic exercise for the maintenance of fat-free mass during dietary restriction, [90][91][92] while aerobic and weight-training exercise in combination was found to be superior to either modality alone for decreasing whole body fat during dietary restriction. 90,93 Theoretically, a similar rationale for preserving fat-free mass would apply when selecting an optimal treatment for overweight in youth.…”
Section: Discussionmentioning
confidence: 99%
“…90,93 Theoretically, a similar rationale for preserving fat-free mass would apply when selecting an optimal treatment for overweight in youth.…”
Section: Discussionmentioning
confidence: 99%
“…2 Although caloric restriction has been the major weight loss strategy, it has been shown that exercise programs designed for fat loss result in an increase in cardiorespiratory fitness 3 and a preservation of fat-free mass. [4][5][6] Most exercise programs designed for weight loss have focused on steady-state exercise (SEE) of around 30 min at a moderate intensity on most days of the week. Disappointingly, these kinds of exercise programs have led to little or no fat loss.…”
Section: Introductionmentioning
confidence: 99%